Sports and energy drinks - Friedhelm Diel; Roman A. Khanferyan (Foods and Raw Materials, 2018)
Presently, sports and energy drinks are widely spread not only among athletes, but also among ordinary people of different ages. The purpose of these beverages is to effectively compensate for the loss of water, energy and electrolytes in the human body before or after some exhausting activities. A questionnaire survey on energy drinks conducted in all eight federal districts of the Russian Federation shows that the younger groups of the Russian population (aged 12–17 and 18–30) drink tonic beverages more often than the older groups (aged 31–45 and 45–60). Further, a recent rise in unreasonable consumption of sports and energy drinks among teenagers may lead to various diseases: obesity, type 2 diabetes, heart disease and tooth enamel erosion. Finally, the authors analyse the composition of energy beverages and thoroughly describe each of their main components (L-carnitine, creatine, caffeine, taurine, and juice-containing products). These components are used by athletes due to their effects: L-carnitine helps reduce the signs of physical and mental overstrain, and stimulates working capacity; creatine improves endurance and anaerobic activity; caffeine raises aerobic endurance by increasing the oxidation of fats, thereby helping preserve glycogen in the muscles; taurine plays an important role as an antioxidant protector in the regulation of Ca++ transport, and as a regulator of osmotic pressure in the tissues.